Influence of Teacher Competence, Motivation and Job Satisfaction on Teacher’s Performance SMP Negeri 1 Cikarang Bekasi Regency East - Niantoro R Sutrisno; H. Puji Isyanto; Rachmat Hasbullah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2016)
The purpose of this study is to identify, analyze and assess influences of Teacher’s Competency, Motivation and Job Satisfaction on Teacher’s Performance at State Junior High School 1 East CikarangBekasi Regency.This research is intended to giving advice for the teacher’s competence, motivation and job satisfaction in order teacher’s performance improve. This research was using descriptive and verification method.Descriptive research is used to describe characteristics of a population or phenomenon being studied. Verification is the research conducted with the aim to prove the truth of a theory on a particular time and place.The results of this research are as follows:1. Range scale of teacher’scompetence isquite good, it need to be improved.2. Range scale of teacher’s motivation is quite high, it need to increased.3. Range scale of teacher’s job satisfaction is quite satisfied, it need to increased.4. Range scale of Teacher’s performance is quite good, it need for improved.5. There is a relationship between teacher’s competence and motivation.6. There is a relationship between teacher’s competence and job satisfaction.7. There is a relationship between motivation and job satisfaction.8. There are both partially and simultaneously influence teacher’s competence, motivation and job satisfaction on teacher’s performance.Keywords: Job Satisfaction, Motivation, Teacher’s Competency, Teacher’s Performance